Arbitrarily 3D Configurable Hygroscopic Robots with a Covalent–Noncovalent Interpenetrating Network and Self‐Healing Ability. Issue 18 (25th March 2019) - Cao, Jie; Zhou, Changlin; Su, Gehong; Zhang, Xinxing; Zhou, Tao; Zhou, Zehang; Yang, Yibo
Abstract: Soft materials that can reversibly transform shape in response to moisture have applications in diverse areas such as soft robotics and biomedicine. However, the design of a structurally transformable or mechanically self‐healing version of such a humidity‐responsive material, which can arbitrarily change shape and reconfigure its 3D structures remains challenging. Here, by drawing inspiration from a covalent–noncovalent network, an elaborately designed biopolyester is developed that features a simple hygroscopic actuation mechanism, straightforward manufacturability at low ambient temperature (≤35 °C), fast and stable response, robust mechanical properties, and excellent self‐healing ability. Diverse functions derived from various 3D shapes that can grasp, swing, close–open, lift, or transport an object are further demonstrated. This strategy of easy‐to‐process 3D structured self‐healing actuators is expected to combine with other actuation mechanisms to extend new possibilities in diverse practical applications. Abstract : An elaborately designed hygroscopic actuator is synthesized with hydrogen bonding and a covalently bonded interpenetrating network. It features straightforward shaping processability at low ambient temperature (≤35 °C), fast and stable response, robust mechanical properties, and excellent self‐healing ability. Therefore, diverse functions derived from various 3D shapes are demonstrated, including grasping, swinging, closing–opening, lifting, or transporting an object.